Network Computing and Information Security Second International Conference, NCIS 2012, Shanghai, China, December 7-9, 2012. Proceedings - Lei, Jingsheng; Wang, Fu Lee.; Li, Mo.; Luo, Yuan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the Second International Conference on Network Computing and Information Security, NCIS 2012, held in Shanghai, China, in December 2012. The 104 revised papers presented in this volume were carefully reviewed and selected from 517 submissions. They are organized in topical sections named: applications of cryptography; authentication and non-repudiation; cloud computing; communication and information systems; design and analysis of cryptographic algorithms; information hiding and watermarking; intelligent networked systems; multimedia computing and intelligence; network and wireless network security; network communication; parallel and distributed systems; security modeling and architectures; sensor network; signal and information processing; virtualization techniques and applications; and wireless network.
Applications of Cryptography -- Authentication and Non-repudiation -- Cloud Computing -- Communication and Information Systems -- Design and Analysis of Cryptographic Algorithms -- Information Hiding and Watermarking -- Intelligent Networked Systems -- Multimedia Computing and Intelligence -- Network and Wireless Network Security -- Network Communication -- Parallel and Distributed Systems -- Security Modeling and Architectures -- Sensor Network -- Signal and Information Processing -- Virtualization Techniques and Applications -- Wireless Network.
Keywords: Computer science; Computer communication systems; Computer system failures; Computer security; Computers; Computer Science; Systems and Data Security; Computer Communication Networks; Computing Methodologies; Information Systems and Communication Service; System Performance and Evaluation; Electronic books